Chronic lymphocytic leukemia, a rare cause of pituitary stalk thickening. Issue 7 (19th April 2020) - Faje, Alexander
Abstract: This case highlights a rare presentation of chronic lymphocytic leukemia (CLL). CNS involvement by CLL is rare, and only 5 cases with pituitary or hypothalamic involvement have previously been reported. Unfamiliarity with this disease complication may lead to a delay in diagnosis and treatment.This case highlights a rare presentation of chronic lymphocytic leukemia (CLL). CNS involvement by CLL is rare, and only 5 cases with pituitary or hypothalamic involvement have previously been reported. Unfamiliarity with this disease complication may lead to a delay in diagnosis and treatment. Abstract : The differential diagnosis for pituitary stalk lesions is broad and includes anatomical variants/congenital anomalies, benign and malignant neoplasms (primary or metastatic), infiltrative and inflammatory disorders, and infection. CLL pituitary infiltration is exceptional, but favoring a second and very rare diagnosis over an unusual manifestation of an actively progressing disease was statistically unappealing.